2016
DOI: 10.1007/s10113-016-1030-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation planning and the use of climate change projections in local government in England and Germany

Abstract: Planning for adaptation to climate change is often regarded to be a local imperative and considered to be more effective if grounded on a solid evidence base and recognisant of relevant climate projections. Research has already documented some of the challenges of making climate information usable in decision-making but has not yet sufficiently reflected on the role of the wider institutional and regulatory context. This article examines the impact of the external institutional context on the use and usability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 42 publications
1
35
0
1
Order By: Relevance
“…The latter is consistent with other studies in Germany that found adaptation plans in one third of the cities [6], and showed that one third of the regional planning authorities considered climate adaptation in their regional plans [23]. In combination with the survey result that climate change adaptation is considered a "relatively new topic" in many municipalities in Baden-Wuerttemberg, our study contributes further evidence to Lorenz et al's conclusion that, "Despite progress on adaptation at [the] national level [in Germany], adaptation at the local level still seems to be in the early stages" ( [58], p. 7). This confirms the "gap between the perceived urgency of proactive adaptation to climate change by scientists and the perceptions of planners" observed in Dutch urban areas ( [12], p. 777).…”
Section: State Of Adaptation In Municipalities Variessupporting
confidence: 76%
See 2 more Smart Citations
“…The latter is consistent with other studies in Germany that found adaptation plans in one third of the cities [6], and showed that one third of the regional planning authorities considered climate adaptation in their regional plans [23]. In combination with the survey result that climate change adaptation is considered a "relatively new topic" in many municipalities in Baden-Wuerttemberg, our study contributes further evidence to Lorenz et al's conclusion that, "Despite progress on adaptation at [the] national level [in Germany], adaptation at the local level still seems to be in the early stages" ( [58], p. 7). This confirms the "gap between the perceived urgency of proactive adaptation to climate change by scientists and the perceptions of planners" observed in Dutch urban areas ( [12], p. 777).…”
Section: State Of Adaptation In Municipalities Variessupporting
confidence: 76%
“…The fact that municipalities use analyses of the current climate and documents such as climate function maps or planning recommendation maps more often than climate projections also has been described in previous studies [23,58]. However, municipalities use (online) information sources frequently to obtain information about future climate change, its effects, and concrete measures for adaptation.…”
Section: Adaptation Often Relies On Previous Experiencesmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in Section 4, communities were interested in adaptation support (not necessarily the Wizard) as long as National Indicator 188 required them to report on local adaptation, and once this requirement ceased to exist their interest in adaptation faded. This implies that adaptation policy support tools do not have the power to promote comprehensive adaptation processes (at least not in small communities), unless they are accompanied by adequate national (or regional) policies (for a similar conclusion on the use of climate projections in local adaptation planning in England and Germany, see Lorenz, Dessai, Forster, & Paavola, ). If support tools are too remote from target group needs (also because accompanying policies shaping these needs are not in place), they perpetuate the notorious dilemma of decision support, namely that policy‐makers find respective tools irrelevant for their work while scientists complain that their outputs remain unused (Reinecke et al, , p. 3, who reference Cash et al, ).…”
Section: Comparison and Conclusionmentioning
confidence: 99%
“…Dat zou een meer omvattend beeld opleveren van toekomstige klimaatrisico's. Engeland was daar een voorbeeld van, hoewel lokale klimaatkennisproductie daar wel is komen stil te staan sinds het ambitieuze reguleringskader uit de Climate Change Act deels is ontmanteld (Lorenz, Dessai, Forster, & Paavola, 2017). Er zou een expertorganisatie kunnen worden opgezet om die beoordeling kritisch te beoordelen.…”
Section: Meekoppelen En Co-creatie: Kritisch (Onder)belichtunclassified